Specular-reflection photonic hook generation under oblique illumination of a super-contrast dielectric microparticle; Journal of Optics; Vol. 23, iss. 4 - Geynts Yu. E. Yury Elmarovich; Zemlyanov A. A. Aleksandr Anatoljevich; Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich (2021, 2021)
Title screen